Exposure to Imidacloprid under variable conditions disturbs the muscle fatty acid profile of a fresh water non target fish: Labeo rohita - Shazia Qadir; Muhammad Latif; Wen-Feng Wu; Fengqin Feng; Wadi B. Alonazi; Arwah Amjad; Chien-Chin Chen; Zia Ur Rehman; Adil Khan; Furhan Iqbal (Animal Biotechnology)
Economy of Pakistan is heavily dependent upon agriculture and extensive use of pesticide is quiet common to enhance the crop yield. Imidacloprid is among the first choice pesticides in Pakistan and it has been reported that through run off along with water it ends up in water bodies affecting non target aquatic fauna. Through the present investigation, we are reporting the effects of Imidacloprid on the fatty acids composition of a non-target, commercially important carp: Labeo rohita. Fish were exposed to sub lethal concentration of Imidacloprid (120 mgL1) for 2, 4 and 8 days (short term) as well as for 16, 32 and 64 days (long term experimental conditions). Pesticide untreated controls were also maintained for each treatment. Following the specific Imidacloprid exposure, fatty acid composition (%) was determined in the muscle of all experimental groups by using gas chromatography. Fish exposed to Imidacloprid for 8 days had reduced Palmitic acid (p = 0.02) and elevated muscle Arachidic acid (p < 0.001) than control group. Labeo rohita exposed to the pesticide for 32 days had elevated muscle Oleic (p = 0.02) and Linoleic acid (p = 0.02) while fish exposed to Imidacloprid to 64 days had reduced muscle Palmitic (p = 0.04) and Oleic acid (p = 0.03). In conclusion, we are reporting that the exposure to sub lethal concentration of Imidacloprid disturb the muscle fatty acid composition of Labeo rohita that may affect its food quality. The effects were more pronounced under long term experimental conditions and were probably due to potentiating lipid peroxidation and disturbed fish metabolism upon Imidacloprid exposure.